Pengaruh Sikap, Pengetahuan, dan Informasi Terhadap Partisipasi Masyarakat Pada Penerapan Program Kerja Badan Usaha Milik Desa (BUMDes) Tri Jenaka di Desa Timuhun - Dewi, Ni Luh Sri Juliana; Suwena, Kadek Rai (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This research aims to determine the effect of community participation on the implementation of the Tri Jenaka Village-Owned Enterprise (BUMDESA) work program in Timuhun Village. This research uses a causal quantitative plan. In this research, the population used was the entire Timuhun Village community, totaling 3415. The sample was determined using the random sampling technique and the Slovin formula, so that a sample of 193 was obtained. This research uses quantitative data using primary data sources obtained through questionnaires and secondary data. obtained from BUMDesa documents or records. Data processing uses the help of the Statistical Package for The Social Science (SPSS) version 25 program. The data analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this research show that (1) attitude has a positive and significant effect on community participation in the implementation of the Tri Jenaka Village-Owned Enterprise (BUMDESA) work program in Timuhun Village, (2) knowledge has a positive and significant effect on community participation in the implementation of the Business Entity work program Village-Owned Enterprises (BUMDESA) Tri Jenaka in Timuhun Village, (3) information has a positive and significant effect on community participation in the implementation of the Tri Jenaka Village-Owned Enterprises (BUMDESA) work program in Timuhun Village and (4) attitudes, knowledge and information have a positive and Simultaneously significant impact on community participation in the implementation of the Tri Jenaka Village-Owned Enterprise (BUMDESA) work program in Timuhun Village.